Chemical exchange saturation transfer imaging for epilepsy secondary to tuberous sclerosis complex at 3 T: Optimization and analysis. (27th May 2021) - Wen, Qingqing; Wang, Kang; Hsu, Yi‐Cheng; Xu, Yan; Sun, Yi; Wu, Dan; Zhang, Yi
Abstract : The homeostasis of various metabolites is impaired in epilepsy secondary to the tuberous sclerosis complex (TSC). Chemical exchange saturation transfer (CEST) imaging is an emerging molecular MRI technique that can detect various metabolites and proteins in vivo . However, the role of CEST imaging for TSC‐associated epilepsy has not been assessed. Here, we aim to investigate the feasibility of applying CEST imaging to TSC‐associated epilepsy, optimize the CEST acquisition parameters, and provide an analysis method for exploring the dominant molecular contributors to the CEST signal measured. Nine TSC epilepsy patients were scanned on a 3‐T MRI system. The CEST saturation frequencies were swept from −6 to 6 ppm with 12 different combinations of saturation power (4, 3, 2 and 1 μT) and duration (1000, 700 and 400 ms). Furthermore, a two‐stage simulation method based on the seven‐pool Bloch‐McConnell model was proposed to assess the contribution of each exchangeable pool to the CEST signal in normal‐appearing white matter and cortical tubers, which avoided the complexity and uncertainty of full Bloch‐McConnell fitting. The results showed that under the optimal saturation duration of 1000 ms, the greatest contrast between tubers and normal tissues occurred around 3, 2.5, 1.75 and 3.5 ppm for B1 of 4, 3, 2 and 1 μT, respectively. At the optimal frequency offsets, the CEST values of tubers were significantly higher than those in the normal brain tissues ( P  < 0.01). Furthermore, the two‐stage analysis suggested that the amine pool played a dominant role in yielding the contrast between cortical tubers and normal tissues. These results indicate that CEST MRI may serve as a potentially useful tool for identifying tubers in TSC, and the two‐stage analysis method may provide a route for investigating the molecular contributions to the CEST contrast in biological tissues. Abstract : An optimized CEST scheme allows the detection of tubers in TSC‐associated epilepsy at 3 T, with an optimal saturation time of 1000 ms, while the optimal saturation frequency offsets were 3, 2.5, 1.75 and 3.5 ppm for saturation powers of 4, 3, 2 and 1 μT, respectively. A two‐stage analysis method was proposed and suggested that the amine pool played a dominant role for the CEST contrast between tubers and normal tissues.